COVID-19-Fear Affects Current Safety Behavior Mediated by Neuroticism—Results of a Large Cross-Sectional Study in Germany - Fink, Madeleine; Bäuerle, Alexander; Schmidt, Kira; Rheindorf, Nadine; Musche, Venja; Dinse, Hannah; Moradian, Sheila; Weismüller, Benjamin; Schweda, Adam; Teufel, Martin; Skoda, Eva-Maria (Frontiers in Psychology, 2021)
Objectives: Although many research studies concerning changes in personality and behavior in time of COVID-19 pandemic emerged, important questions still have not been answered. This study with a large sample aimed to give insights into the impact of personality on pandemic fear and behavior by investigating the Big Five traits, COVID-19-fear, and associated behavioral changes in a large German-speaking sample. Methods: About 14,048 healthy respondents (65.5% female, 34.2% male, and 0.32% other gender/gender queer; range = 18–85 years, median age 35–44 years) participated in the survey during the COVID-19 pandemic. Two scales, “adherent” safety behavior (ASB, α = 0.857) and “dysfunctional” safety behavior (DSB, α = 0.876), three items each, measured pandemic-associated behavior. The Big Five Inventory-10 (BFI-10) tested personality traits. Results: While ASB correlated negatively with extraversion (rho = −0.053, ≤ 0.001), the other four traits were positively associated, with the highest association for neuroticism (rho = 0.116, ≤ 0.001), whereas neuroticism showed a positive correlation (rho = 0.142, ≤ 0.001) with DSB, extraversion (rho = −0.042, ≤ 0.001), agreeableness (rho = −0.028, ≤ 0.001), and conscientiousness (rho = −0.025, ≤ 0.001) correlated negatively with it. Regression analyses showed a small extent of the effect of personality traits. Moreover, neuroticism mediated the association between COVID-19-fear and DSB (positive-directed). Conclusions: Even though our results on correlations between personality, pandemic fear, and related behavior are in line with the existing literature studies, the analyses clearly show that the impact of personality traits, including neuroticism, on pandemic behavior is very small. Rather, pandemic fear has a much larger influence on the safety behavior mediated through neuroticism. Further studies should bear in mind that personality traits can not only have influencing effects but also mediating effects.